2001
DOI: 10.1200/jco.2001.19.13.3203
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-Induced Pathologic Necrosis: A Predictor of Local Recurrence and Survival in Patients Receiving Neoadjuvant Therapy for High-Grade Extremity Soft Tissue Sarcomas

Abstract: Treatment-induced pathologic necrosis is an independent predictor of both local recurrence and overall survival in patients who receive neoadjuvant therapy for high-grade extremity soft tissue sarcomas. A complete pathologic response (> or = 95% pathologic necrosis) correlated with a significantly lower rate of local recurrence and improved overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
228
3
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(242 citation statements)
references
References 28 publications
9
228
3
2
Order By: Relevance
“…69 On the basis of these results, the authors concluded that the extent of pathologic necrosis may be considered a surrogate endpoint for survival outcomes in patients with soft tissue sarcomas. 73 The ways in which a response to induction therapy (eg, radiation therapy or chemotherapy) translates into other clinically meaningful outcomes (eg, reduction in the scope of surgical resection) are also not well defined. A recent retrospective analysis did examine the impact of preoperative chemotherapy on the scope of surgery.…”
Section: Preoperative Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…69 On the basis of these results, the authors concluded that the extent of pathologic necrosis may be considered a surrogate endpoint for survival outcomes in patients with soft tissue sarcomas. 73 The ways in which a response to induction therapy (eg, radiation therapy or chemotherapy) translates into other clinically meaningful outcomes (eg, reduction in the scope of surgical resection) are also not well defined. A recent retrospective analysis did examine the impact of preoperative chemotherapy on the scope of surgery.…”
Section: Preoperative Chemotherapymentioning
confidence: 99%
“…The incidence of treatmentinduced pathologic necrosis and its correlation with clinical outcomes are also not well defined in Soft Tissue Sarcomas patients with soft tissue sarcomas. 73 Small studies have shown complete pathologic tumor necrosis occurring in only 5% to 9% of the patients receiving doxorubicin-based induction chemotherapy. 74 -76 In addition, in a retrospective analysis of 496 patients with intermediate-and high-grade extremity soft tissue sarcomas who were treated with preoperative therapy (consisting primarily of doxorubicin-based chemotherapy and radiation therapy), complete pathologic responses (greater than or equal to 95% necrosis) were noted in only 69 patients (14%).…”
Section: Preoperative Chemotherapymentioning
confidence: 99%
“…1 Response to NeoCT is usually monitored using serial cross-sectional imaging. Although the pathologic response to NeoCT is a predictor of local recurrence and survival, 2 this information is available only after surgical resection. Although preoperative patient management decisions are based on the radiographic response to therapy, there is no consensus among studies that this response correlates with survival.…”
mentioning
confidence: 99%
“…Several non-randomized trials showed high rates of histological response [48,49] up to~50%, which correlated with outcome including overall survival [48]. Delaney et al [50] and Mullen et al [51] also described excellent results in a highly unfavourable patient group after treatment with an intensified regimen of neoadjuvant chemoradiation at Massachusetts General Hospital (MGH), although considerable rates of toxicity were observed.…”
Section: Discussionmentioning
confidence: 99%